2008
DOI: 10.1016/j.biocel.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Photolon™, a chlorin e6 derivative, triggers ROS production and light-dependent cell death via necrosis

Abstract: PhotolonTM is a photosensitiser with demonstrated potential as an anti-tumour agent. In this study, an in vitro investigation was performed to determine the mechanism of Photolon TM -induced cell death. Cell killing was observed in a light-dependent manner and light-activated Photolon TM resulted in a significant production of reactive oxygen species (ROS), which could be blocked by type I ROS scavengers. Inhibition of ROS production using Trolox prevented Photolon TM -induced cell death. Lightactivated Photol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…As it was created by joining Ce6 and PVP, Photolon features better stability and solubility in water and, therefore, also better bioavailability than Ce6 alone [18]. Comparisons of the Ce6-PVP complex with pure Ce6 also demonstrated a higher ability of the compound to accumulate in neoplastic tissue and faster removal time from the body [18].…”
Section: Original Papersmentioning
confidence: 99%
“…As it was created by joining Ce6 and PVP, Photolon features better stability and solubility in water and, therefore, also better bioavailability than Ce6 alone [18]. Comparisons of the Ce6-PVP complex with pure Ce6 also demonstrated a higher ability of the compound to accumulate in neoplastic tissue and faster removal time from the body [18].…”
Section: Original Papersmentioning
confidence: 99%
“…For this reason, there has been an increased interest in developing PDT for local infections treatment. Different types of PS have been proposed in laboratory investigations, including porphyrins [14,15], phenothiazine dyes [16,17], chlorins [18,19], and phthalocyanines [20]. However, complete killing of the microorganisms is not frequently achieved and some of the available PS showed limited effectiveness against Candida biofilms and animal models of candidiasis [15,21].…”
Section: Introductionmentioning
confidence: 99%
“…Upconversion nanoparticle-mediated PDT induces ThP-1 macrophage apoptosis [25][26][27] have demonstrated that PDT induces both apoptosis and necrosis depending on the drug concentrations as well as the laser irradiation time and intensity. In this study, we evaluated the type of cell death that occurred following UCNPs-Ce6-mediated PDT using three different methods.…”
mentioning
confidence: 99%